Information systems for crisis response and management in Mediterranean Countries : 4th International Conference, ISCRAM-med 2017, Xanthi, Greece, October 18-20, 2017, Proceedings /: 4th International Conference, ISCRAM-med 2017, Xanthi, Greece, October 18-20, 2017, Proceedings. (2017) - Unknown
No abstract available